Studi Ketahanan Pangan Rumah Tangga Petani Lahan Kering di Desa Sekotong Barat Kecamatan Sekotong Kabupaten Lombok Barat - Rusdiani, Rusdiani; Hayati, Hayati; Muktasam, Muktasam (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Disparities in the availability and diversity of food consumption are caused, among other things, by regional conditions and land agro-ecosystems. The objectives of this research are 1) to determine the income and expenditure of dry land farming households and 2) to analyze the level of food security of dry land farming households in Sekotong Barat Village. The research method was carried out descriptively. The number of dry land farmers in Sekotong Barat Village is 180 households and 30 farming households were selected using simple random sampling. The results of the research show: 1) The household income of dry land farmers is IDR 42,511,641 per year which comes from farming income (on-farm) IDR 29,303,641, off-farm IDR 4,068,000, non-farm IDR 4,080,000, and income from other sources IDR 5,060,000 per year. 2) The total expenditure of dry land farming households is IDR 38,457,892 per year and allocated for food expenditure IDR 33,617,092 and non-food IDR 4,840,800 per year and 3) Level of food security Dry land farming households fall under the "Food Security" criteria. Then the level of food security in each household, 56.67% are classified as "Food Insecure" and 43.33% are classified as "Not Food Insecure.